Beyond the Margins: Analyzing Social Exclusion with a Homeless Client Dataset - Javier Ramos Diaz; Albert Varela (Social Work & Society, 2011)
A great share of literature on social exclusion has been based mainly on the analysis of official survey data. Whereas these efforts have provided insights into the characteristics and conditions of those people living at the margins of mainstream social relations, they have however failed to encompass those who live beyond these very margins. Meanwhile, research on these hidden subpopulations, such as homeless and other vulnerable groups, remains generally less abundant and is significantly detached from the theoretical core of the debate on social exclusion. The concern about these shortcomings lies at the heart of our research. We seek to bring some light to the area by using data made available by an organization that provides services to people experiencing homelessness in Barcelona (Spain). The data sample contains clients in early stages of exclusion and others in chronic situations. Thus, we attempt to identify some of the variables that operate in preventing the "chronification" of those individuals in situation of social exclusion. Our findings suggest that certain variables such as educational level, income and housing type, which are considered to be central predictors in the analysis of poverty, behave differently when analyzing differences between stages of social exclusion. Although these results cannot be extrapolated to the whole Spanish or European reality, they could provide useful insight for future investigations on this topic.